Some Afro-Asian Deserts, Aspects of Their Origin, Ecobiology and Reclamation - Kadambi, K (Annals of Arid Zone, 2016)
Every ecological factor of a desert operates against the establishment and progress of vegetation. Desert techniques have to meet the challenge of nature, often severe. obstinate and ruthless. Even the first step, that of mapping the desert land mass, has its problems; the topography of a desert surface constantly shifts and meanders. Water, source of all life, is scarcer here than elsewhere, and often not a blade of grass or a stick of fodder is found. Eco-biology of the arid lands and classification of desert have been discussed with reference to the impact of Solar energy "Vegetation efficiency" of deserts. Suggestions and proposals for the afforestation of arid lands have been made. The largest of world’s deserts is alone larger than the Australian continent, and this continent itself holds an expansive desert. There is but one solution for this, the mightiest of ’problems facing man; the swish of desert winds driving the piping sands before them could alone be stilled by the flutter of green leaves rooted on the sands, There is, therefore, urgent need for a Saharan university with affiliated schools of forestry to train down-to-earth technicians able to tackle problems of agriforestation of arid lands& The research wing of the university should undertake ad hoc research on practical problems, avoiding research of a theoretical nature.